2019
DOI: 10.1007/s40506-019-00190-9
|View full text |Cite
|
Sign up to set email alerts
|

The Present and Future State of Antimicrobial Stewardship and Rapid Diagnostic Testing: Can One Ideally Succeed Without the Other?

Abstract: Purpose of review The growth and development of rapid diagnostic technologies (RDTs) in infectious diseases (ID) have grown significantly over the past several years. The aim of these platforms is to identify causative pathogens more quickly and target antimicrobial therapy earlier, ultimately improving patient outcomes. Use of RDT specifically from blood specimens to optimize antimicrobial therapy and improve patient outcomes is a recommendation by the most recent antimicrobial stewardship (AMS) guidelines. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…An important strategy to reduce AMR is the use of rapid diagnosis for bacterial infections. Studies have shown that the use of rapid diagnosis methods for bacterial infections as part of ASP can improve the time to optimal antibiotic therapy, decreasing the rate of recurrent infection, mortality, hospital duration and hospital costs [ 115 ].…”
Section: Healthcare Associated Infectionsmentioning
confidence: 99%
“…An important strategy to reduce AMR is the use of rapid diagnosis for bacterial infections. Studies have shown that the use of rapid diagnosis methods for bacterial infections as part of ASP can improve the time to optimal antibiotic therapy, decreasing the rate of recurrent infection, mortality, hospital duration and hospital costs [ 115 ].…”
Section: Healthcare Associated Infectionsmentioning
confidence: 99%
“…These systems vary in number of pathogens identified and resistance mechanisms detected and are meant to be used in conjunction with traditional antimicrobial susceptibility testing methods. Table 1 provides a summary of the RDTs for detecting Gram‐negative bacteria currently available in the United States 16‐26 . The technologies primarily utilize single and multiplex polymerase chain reaction (PCR, mPCR) to rapidly identify bacteria and/or resistance mechanisms by detecting specific DNA and/or protein sequences.…”
Section: Rapid Diagnostics For Gram‐negative Bloodstream Infectionsmentioning
confidence: 99%
“…Each system has strengths and weaknesses (Table 2). 23,24,26–28 Local epidemiology, resistance patterns, and target patient population can help clinicians determine which system(s) to employ.…”
Section: Rapid Diagnostics For Gram‐negative Bloodstream Infectionsmentioning
confidence: 99%
“…El desarrollo de nuevas técnicas de diagnóstico microbiológico que permiten la identificación del microorganismo causal en menor tiempo está permitiendo optimizar el consumo de antimicrobianos. Dentro de estas pruebas destacan las técnicas de diagnóstico virológico rápido en muestras respiratorias 3 .…”
Section: Introductionunclassified